Cumulative Association of Twenty-Two Genetic Variants with Seropositive Rheumatoid Arthritis Risk - Karlson, Elizabeth W. (2010)
BACKGROUND: Recent discoveries of risk alleles have made it possible to define genetic risk profiles for patients with rheumatoid arthritis (RA). We examined whether a cumulative score based on 22 validated genetic risk alleles for seropositive RA would identify high-risk, asymptomatic individuals who might benefit from preventive interventions. METHODS: We genotyped 14 single nucleotide polymorphisms (SNPs) at 13 validated RA risk loci and 8 HLA alleles among (1) 289 Caucasian seropositive cases and 481 controls from the US Nurses' Health Studies (NHS), and (2) 629 Caucasian CCP antibody positive cases and 623 controls from the Swedish Epidemiologic Investigation of RA (EIRA). We created a weighted genetic risk score (GRS), where the weight for each risk allele is the log of the published odds ratio. We used logistic regression to study associations with incident RA. We compared AUCs from a clinical-only model and clinical + genetic model in each cohort. RESULTS: Patients with GRS > 1.25 standard deviations of the mean had a significantly higher OR of seropositive RA in both NHS (OR=2.9, 95%CI 1.8–4.6) and EIRA (OR=3.4, 95% CI 2.3–5.0) referent to the population average. In NHS, the AUC for a clinical model was 0.57 and for a clinical + genetic model was 0.66, and in EIRA was 0.63 and 0.75, respectively. CONCLUSION: The combination of 22 risk alleles into a weighted genetic risk score significantly stratifies individuals for RA risk beyond clinical risk factors alone. However, given the low incidence of RA, the clinical utility of a weighted genetic risk score is limited in the general population.